2012
DOI: 10.1111/ejh.12009
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the vascular endothelial growth factor in hematologic malignancies

Abstract: There exists increasing evidence that apart from solid tumors, angiogenic growth factors also play important roles in the development and/or maintenance of hematolymphoid malignancies. Thus, in these cancers, angiogenesis and bone marrow microvessel density often correlate with prognosis and disease burden. Several reports speculated on the role of angiogenesis and the resulting possible therapeutic options in hematologic malignancies. The most prominent angiogenic factor, vascular endothelial growth factor (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 119 publications
(204 reference statements)
0
6
1
Order By: Relevance
“…Angiogenesis factors are involved in the pathogenesis of most of the hematologic malignancies, and raised circulating VEGF levels have been described in chronic myeloid leukemia, chronic myelomonocytic leukemia, chronic lymphocytic leukemia, and lymphoma, often in correlation with disease activity. 12 14 The VEGF level has previously been found elevated in multiple myeloma (MM), 15 but our study found lower sVEGF concentrations in this group in comparison to other HD groups and to patients with no HD; this finding might be due to a large proportion (16/18) of treated patients in our cohort. 15 Increased VEGF levels has also been described in WM in 1 study.…”
Section: Discussioncontrasting
confidence: 66%
“…Angiogenesis factors are involved in the pathogenesis of most of the hematologic malignancies, and raised circulating VEGF levels have been described in chronic myeloid leukemia, chronic myelomonocytic leukemia, chronic lymphocytic leukemia, and lymphoma, often in correlation with disease activity. 12 14 The VEGF level has previously been found elevated in multiple myeloma (MM), 15 but our study found lower sVEGF concentrations in this group in comparison to other HD groups and to patients with no HD; this finding might be due to a large proportion (16/18) of treated patients in our cohort. 15 Increased VEGF levels has also been described in WM in 1 study.…”
Section: Discussioncontrasting
confidence: 66%
“…Intriguingly, the OGU1 cells expressed VEGF mRNA and protein in the cell culture supernatant. The expression of VEGF and VEGFR has been reported in various hematological malignancies including lymphomas . However, it is not completely understood how VEGF contributes to the pathogenesis of the lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…All these proangiogenic agents act through distinct membrane receptors [28,29] which result in the activation of extensively overlapping intracellular cascades finally activating common effector molecules, such as NF-κB or HIF-1 [28]. In addition, recent evidences indicate that direct interactions may occur between integrin activated pathways and signalling from VEGF receptors [30] and EGF receptors [31]. Collectively, in the light of such observations, our results support the ability of cyclo [DKP-RGD] 1 to block common mechanisms, resulting in the effective inhibition of angiogenesis triggered by multiple agents.…”
Section: Discussionmentioning
confidence: 99%